The Heavy Metal Contamination in Shallow Groundwater at Coastal Areas of Surabaya East Java Indonesia - Baskoro Rochaddi; Warsito Atmodjo; Alfi Satriadi; Chrisna Adhi Suryono; Irwani Irwani; Sugeng Widada (Universitas Diponegoro, 2019)
The present study was conducted to assess the level of heavy metal contamination in shallow aquifer of Surabaya coastal areas. Six heavy metals (Arsenic, Mercury, Chromium, Lead, Cupper and Magnesium) of contaminant have been determined in the shallow groundwater. The samples were then analyzed by using Atomic Absorbent Spectrometry gas and followed by using the method of Standard Method Examination. The result indicated that shallow groundwater in Surabaya has been contaminated by Arsenic (0.243 ppm) and Magnesium (1.262 ppm). Another heavy metal such as Mercury, Chromium, Lead, and Cupper showed bellow detected. This study has proven the presence of heavy metal as specially Arsenic and Magnesium has been contain in shallow aquifer supplies in the coastal areas of Surabaya.